IMPROVING MECHANISMS OF MANAGING INNOVATION PROCESSES AT SERVICE ENTERPRISES (IN CASE OF UZBEK HOTELS) - Hudayberdiyeva Nargiza Nizomiddin Qizi (Journal of Artificial Intelligence and Digital Economy, 2024)
Background: Service innovation is critical for enhancing competitiveness and customer satisfaction in the hospitality industry, particularly within hotel enterprises. Specific Background: This article examines the theoretical foundations of service innovation and its significance in the hotel sector, integrating insights from both international research and local practices in Uzbekistan. Knowledge Gap: Despite the growing recognition of service innovation, there is a lack of comprehensive studies that address the unique challenges and opportunities faced by hotels in Uzbekistan compared to global trends. Aims: The aim of this article is to analyze existing literature on hotel economy and service innovation, highlight successful service innovation practices from leading global hotels, and propose actionable recommendations for Uzbek hotel businesses. Results: The review of foreign research, coupled with case studies of innovative practices in both international and Uzbek hotels, reveals key trends and strategies that can be adapted to the local context. Novelty: This work contributes to the existing literature by providing a comparative analysis of global service innovations and their applicability to the Uzbek hospitality sector, thus filling a significant research gap. Implications: The findings underscore the importance of adopting innovative practices to enhance service delivery and operational efficiency in Uzbek hotels, offering valuable insights for stakeholders aiming to improve their competitive edge in the evolving hospitality landscape. Ultimately, the article concludes with recommendations grounded in both international and national experiences in service innovation management, guiding future initiatives in the Uzbek hotel industry.